2008
DOI: 10.1152/ajpregu.00412.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline reduces neutrophil-epithelial interactions in vitro and gut tissue damage in a mouse model of colitis

Abstract: Hypertonic saline (HS) exerts various inhibitory effects on PMN function. We hypothesized that HS could inhibit transepithelial migration of PMN and thereby prevent inflammatory events in experimental colitis. Isolated human PMN were treated with HS (40 mM), and their transmigration across a monolayer of T84 epithelial cells was induced by N-formyl-methionyl-leucyl-phenylalanine. Monolayer disruption was assessed by monitoring changes in transepithelial conductance in an Ussing chamber. Colitis in mice was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Tillinger et al investigated HS treatment of neutrophils in vitro . They noted a dose-dependent effect involving decreased cell migration and the disruption of T84 monolayers compared with untreated control cells ( 82 ). Compared with physiological saline, Oreopoulos et al found inhibition of ischemia/reperfusion-induced hepatic expression of ICAM-1 mRNA with HS from in vivo model of hepatic ischemia-reperfusion and in vitro model from the activated endothelial cell.…”
Section: Discussionmentioning
confidence: 99%
“…Tillinger et al investigated HS treatment of neutrophils in vitro . They noted a dose-dependent effect involving decreased cell migration and the disruption of T84 monolayers compared with untreated control cells ( 82 ). Compared with physiological saline, Oreopoulos et al found inhibition of ischemia/reperfusion-induced hepatic expression of ICAM-1 mRNA with HS from in vivo model of hepatic ischemia-reperfusion and in vitro model from the activated endothelial cell.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of 1 mL of 0.9% NaCl corresponds with a dose of approximately 40 mL/kg of NaCl solution, which according to previous reports is considered hypertonic when given in a single injection [46]. Hypertonic saline solutions were previously shown to improve the DAI in DSS-treated mice, which was associated with reduced inflammation on day 7 [46]. In our hands, fluid supplementation had no effects on any parameter associated with inflammation on day 7 suggesting that epithelial restitution occurred during the phase of recovery.…”
Section: Discussionmentioning
confidence: 99%